Assessment of the Minimum Clinically Important Difference in Symptoms and Functions of Patients With Acute Schizophrenia: A Post hoc Analysis of an Open-Label, Single-Arm Multicenter Study - Si, Tianmei; Shi, Chuan; Sun, Ling; Zhang, Yilong; Zhang, Lili (Frontiers in Psychiatry, 2021)
The purpose of this study was to evaluate the application of the minimum clinically important difference (MCID) concept to clinical results in Chinese patients with acutely exacerbated schizophrenia. The original study was an 8-week, open-label, single-arm, multicenter study of flexible doses of paliperidone-extended release (pali-ER) in Chinese patients with acutely exacerbated schizophrenia. To determine the MCID value of PANSS, PSP and evaluate the responsiveness of each outcome measurements in the acute phase of schizophrenia. The responsiveness of the four measurements (PANSS, PANSS reduction rate, PSP, CGI-S) were analyzed. 499 patients completed the 8-week follow-up and were finally used for this post hoc analysis. The MCID calculated by different approaches varied from 14.02 to 31.50 for PANSS, 15.14% to 42.79% for PANSS reduction rate, and 7.62% to 13.13% for PSP. In addition, the improvement of the CGI-S owned the highest responsiveness of the four outcome measurements. The threshold value of MCID for schizophrenia patients was determined by choice of the assessment method to extent. In addition, the CGI-S score appeared to be the most valid and responsive measure of effectiveness for the acute phase of schizophrenia.